1999
DOI: 10.1207/s15327914nc340114
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidants and Lung Cancer Risk: A Case-Control Study in Uruguay

Abstract: To examine the protective role of dietary antioxidants (carotenoids, vitamin C, vitamin E, glutathione, and flavonoids) in lung cancer risk, a case-control study involving 541 cases of lung cancer and 540 hospitalized controls was carried out in Uruguay. The relevant variables were energy adjusted using the residuals method and then categorized in quartiles. Adjusted odds ratios (ORs) for antioxidants were calculated through unconditional logistic regression. With the exception of lycopene and vitamin C, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
3
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 30 publications
8
89
3
5
Order By: Relevance
“…The evidence is strongest for an inverse association of total flavonoids, foods rich in flavonoids and quercetin, with lung cancer risk (Hirvonen et al, 2001;Knekt et al, 2002;De Stefani et al, 1999;Le Marchand et al, 2000a). A single study examined rectal cancer, which reported a halving of risk associated with high versus low catechin intake (Arts et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence is strongest for an inverse association of total flavonoids, foods rich in flavonoids and quercetin, with lung cancer risk (Hirvonen et al, 2001;Knekt et al, 2002;De Stefani et al, 1999;Le Marchand et al, 2000a). A single study examined rectal cancer, which reported a halving of risk associated with high versus low catechin intake (Arts et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Total flavonoids and quercetin were associated with a 30-42% reduced risk of lung cancer in two published studies but a non-significant increased risk for lung cancer in a third study (Garcia-Closas et al, 1998;De Stefani et al, 1999;LeMarchand et al, 2000b). With regard to other flavonoids, high versus low quercetin and kaempferol intakes were associated with 40% and 50% reduction in risk, respectively, for stomach cancer.…”
Section: Case-control Studies Of Flavonoids and Cancer Riskmentioning
confidence: 95%
See 1 more Smart Citation
“…42,45 In 9 population studies, all cases of lung cancer death were found to have low serum BC levels, compared to surviving lung cancer patients, whereas only a few cases of lung cancer death had lower serum levels of RE and AT. 46 In the present study, trends in serum RE levels differed between sexes; the OR for men decreased at serum RE levels greater than 3.23 mol/L.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…They have been shown to exert beneficial effects on human health and play an important role in prevention and/or treatment of several serious diseases, such as cancer, inflammation and cardiovascular disease (Middleton et al, 2000;Rice-Evans, 2001). Flavonoids are important beneficial components of food, pharmaceuticals, cosmetics and various commodity preparations due to their antimutagenic, hepatoprotective (Stefani et al, 1999), antiallergic (Berg & Daniel, 1988), antiviral (Middleton & Chithan, 1993) and antibacterial activity (Tarle & Dvorzak, 1990;Tereschuk et al, 1997;Singh & Nath, 1999;Quarenghi et al, 2000;Rauha et al, 2000). They are known to inhibit nucleic acid synthesis (Plaper et al, 2003;Cushnie & Lamb, 2006), cause disturbance in membranes (Stepanovic et al, 2003;Stapleton et al, 2004;Cushnie & Lamb, 2005) and affect energy metabolism (Haraguchi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%